ANALISIS KEKUATAN UNSUR ITIKAD BAIK PADA PELAKSANAAN PENDAFTARAN MEREK DI INDONESIA (Studi Kasus Putusan Mahkamah Agung Nomor 364K/Pdt.Sus-HKI/2014) BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 - Wilson Wijaya; Christine S.T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2018)
Brand is one part of intellectual property rights. Brand is an identifying mark that distinguishes one's property with another's property. However, there are many parties who have bad faith and want to be a part of other people brand’s fame. So they use the same brand name in order to make the goods produced is well-known. Brand is regulated in law number 20 2016 about brand and Geographical Indication. Therefore we need to register our brand to avoid the parties who have bad faith. The authors want to discuss the issue of the strength of good faith element in the registration of trademarks in the implementation of registration in Indonesia and also the protection for brand holders whose registration are rejected in Indonesia. Author will use normative method and refer to scientific books. The strength of good faith element in registering can be seen in Article 4 of the Trademark and Geographical Indications. For protection, brand holder can register it in advance, if it has been approve, the brand holder can submit claim cancelation that regulated in Article 77 to the Central Jakarta District Court to be reviewed and decided who the trademark is and be prove who has the element of bad faith. It is suggested that the original trademark owner's to register their trademark at brand office Indonesia. For foreign trademark owner, they can also improve their trademark to be a well-known brand.